Crystal structure of the dinuclear mercury(II) complex bis(μ2-bromido)-dibromido-bis{1-[(benzotriazol-1-yl)methyl]-1-H-1,3-(2-ethyl-5-methyl-imidazol)-κ1 N} dimercury(II), C26H30N10Hg2Br4 - Yang Hai-Yan; Liu Hong-Yan; Zhao Yao-Min (Zeitschrift für Kristallographie - New Crystal Structures)
C26H30N10Hg2Br4, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 8.8582(4) Å, b = 11.5968(5) Å, c = 17.4657(10) Å, α = 107.564(5)°, β = 92.283(4)°, γ = 97.388(4)°, V = 1690.47(15) Å3, Z = 2, R gt(F) = 0.0423, ωR ref(F 2) = 0.1112, T = 293 K.